PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN KEMAMPUAN SISWA MENDESKRIPSIKAN KONDISI FISIK WILAYAH DAN PENDUDUK INDONESIA - Suharyati, Eny Ike (UNIVERSITAS SLAMET RIYADI, 2016)
The aim of the research is to improve students' ability in describing physical condition of area andcitizen through cooperative learning at the eighth I grade of SMP Negeri 26 Surakarta in the academicyear of 2015/2016.The method of the research is a classroom action research. The source of the data acquired fromthe students, the teacher, interaction among them, and in the classroom. The method of collecting the dataused tests and observation. To check data validity, she used investigator triangulation. Meanwhile, thetechnique of analyzing the data used critical descriptive analysis. The procedure of the research isthrough two cycles, and every cycle consists of planning, acting, observing, and reflecting.The result of the research showed that achievement of the students improved. In fact, from 27students, 5 students (29.02%) completed the achievement and 22 students (70.98%) did not complete, sothe mean score was 61.73. In the cycle one, there were 10 students (53.42%) who completed theachievement, and 17 students (46.58) did not complete, so the mean score was 68.15. In the cycle two, thestudents completed the achievement (100%) so the meanscore was 76.88. Therefore, based on the result ofthe research, it could be concluded that learning through cooperative learning can improve theachievement in using the teaching material